Nicotine Modulates Cognitive Function in D-Galactose-Induced Senescence in Mice - Majdi, Alireza; Sadigh-Eteghad, Saeed; Talebi, Mahnaz; Farajdokht, Fereshteh; Erfani, Marjan; Mahmoudi, Javad; Gjedde, Albert (Frontiers in Aging Neuroscience, 2018)
Here, we tested the claim that nicotine attenuates the signs of brain dysfunction in the model of brain ageing induced by d-galactose (DGal) in mice. We administered nicotine at doses of 0.1, 0.5, and 1 mg/kg by the subcutaneous (s.c.) or at 0.1 mg/kg by the intranasal (i.n.) routes in mice that had received DGal at the dose of 500 mg/kg s.c. for six weeks. We assessed animal withdrawal signs as the number of presented somatic signs, thermal hyperalgesia, elevated plus maze, and open field tests. We evaluated spatial memory and recognition with Barnes maze and novel object recognition tests. We tested brain tissue for reactive oxygen species, mitochondrial membrane potential, caspase-3, Bax, Bcl-2, cytochrome c, brain-derived neurotrophic factor and nerve growth factor levels. Nicotine administration in model groups (0.5 mg/kg s.c. and 0.1 mg/kg i.n. doses) significantly attenuated impairment of spatial and episodic memories in comparison to normal saline-received model group. These doses also reduced mito-oxidative damage as well as apoptosis and raised neurotrophic factors level in model groups in comparison to normal saline-received model group. The 1 mg/kg s.c. dose nicotine revealed withdrawal signs compared with the other nicotine-received groups. Nicotine at specific doses and routes has the potential to attenuate age-related cognitive impairment, mito-oxidative damage, and apoptosis. The doses raise neurotrophic factors without producing withdrawal signs.